PENGARUH PEMBERIAN LIMBAH CAIR TAHU DAN MULSA ORGANIK TERHADAP PERTUMBUHAN PEMBIBITAN TANAMAN KAKAO (Theobroma cacao L.) - Saputra, Indra Nugraha Anom; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of this research is to know the effect of giving tofu liquid waste and rice straw mulch and to get the best interaction between liquid waste know and rice straw mulch for growth of cocoa seed (Theobroma cacao L.). The research was conducted at Balai Benih Induk Hortikultura (BBIH) (BBIH) Marpoyan Damai Pekanbaru. The study was conducted for three months from November 2016 until January 2017, implemented by Randomized Complete Design (RAL) Factorial consisting of 2 factors and 3 replications. The first factor of tofu liquid waste (T) consists of 4 levels: T0 = without tofu liquid waste, T1 = Tofu Liquid waste with concentration 60% / plant, T2 = Tofu liquid Waste with 80% concentration / plant, T3 = 100% / plant. The second factor of rice straw mulch (M) consists of 4 levels: M0 = Without mulch of rice straw, P1 = rice straw mulch of 6.25 g / plant (5 ton / ha), M2 = rice straw mulch of 12.5 g / plant (10 tons / ha), M3 = rice straw mulch of 18.75 g / plant (15 tons / ha). Each unit consists of 2 plants. The observed parameters were plant height, stem diameter, leaf number, soil temperature, soil moisture, root volume, canopy crown weight, crown dry weight, wet root weight, root dry weight, leaf wet weight, leaf dry weight, wet weight of stem, weight Dry stem, leaf area and root canopy ratio. The results showed 100% wetland / plant waste interaction and 6.25 g / plant rice straw mulch in cocoa breeding resulted in root volume, root dry weight, leaf wet weight and leaf area were highest compared to other treatments. Keywords: Liquid Waste Tofu, Rice Straw Mulch, cocoa seed